Urgensi Aplikasi Teknologi dalam Pendidikan di Indonesia - Miko Trenggono Hidayatullah; Masduki Asbari; Muhammad Iqbal Ibrahim; Ahmad Hadidtia Haekal Faidz (AGUSPATI RESEARCH INSTITUTA, 2023)
The objective of this study is to investigate various technologies that can be implemented in the context of education in Indonesia. This research report employs a qualitative descriptive method by conducting a listening and note-taking approach, as the data source is derived from listening to the oral narration on the YouTube channel Jabfung PTP titled